Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Correct option is
B
(1−3a−3b)(1+a+b)
1−2a−2b−3(a+b)
2
=−3(a+b)
2
−2(a+b)+1
=−3(a+b)
2
−3(a+b)+(a+b)+1
=−3(a+b)((a+b)+1)+((a+b)+1)
=((a+b)+1)(1−3(a+b))
=(a+b+1)(1−3a−3b)
Answer:
[tex]-3.5[/tex]
Step-by-step explanation:
[tex](a-2b)^{3} \\=a^{3}-6a^{2} b+6ab^{2}-8b^{3}[/tex]
Given that,
[tex]a=(-3)\\b=(-1/2)[/tex]
So,
[tex](a-2b)^{3} \\=a^{3}-6a^{2} b+6ab^{2}-8b^{3}\\=(-3)^{3}-6* (-3)^{2} *\frac{-1}{2} +6*(-3)*(\frac{-1}{2} )^{2} -8*(\frac{-1}{2} )^{3} \\= (-27)-6*9*\frac{-1}{2} +-18*\frac{1}{4} -8*\frac{-1}{8} \\=(-27)-6*-4.5-4.5+1\\=-27+27-4.5+1\\=-3.5[/tex]
Hope this helps you
Let me know if you have any other questions :-)
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.